Arabic Qur’anic Near-Synonymy: A Corpus-Based Analysis of Al-Raghib Al-Aṣfahani’s Mufradat Alfaẓ Al-Qur’an - Uyuni, Yuyun Rohmatul; Nuryulia, Siti; Milah, Aang Saeful; Mu'izzudin, Moch; Hawari, Agna (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2026)
This study of Qur’anic vocabulary emphasizes the importance of examining near-synonymy to uncover subtle semantic distinctions in Arabic discourse. Although classical lexicographers have addressed synonymy extensively, corpus-based analyses of Qur’anic near- synonymy remain limited. This study analyzes semantic differentiation, syntactic patterns, and lexical distribution in selected near-synonymous pairs found in Al-Raghib al- Asfahani’s Mufradat Alfaz al-Qur'an, focusing on khawf– khashyah, ghaḍab–sakhaṭ, ḥuzn–asā, qalb–fuʾād, and ʿilm–maʿrifah. The primary data source consists of a verified digital (.txt) edition of Mufradāt Alfāẓ al-Qur’ān, cross-checked against a printed critical edition to ensure textual reliability. The corpus includes all lexical entries related to the selected pairs. The dataset was processed using AntConc and Sketch Engine to extract concordance lines, collocational patterns, and frequency distributions. The results reveal consistent semantic and functional distinctions across the pairs. For instance, khawf appears in broader experiential contexts, while khashyah is associated with reverential awareness; ghaḍab denotes emotional anger, whereas sakhaṭ conveys divine disapproval. Similar differentiation is observed in the remaining pairs in terms of meaning, syntactic behavior, and thematic distribution. These findings demonstrate that integrating classical Arabic lexicography with corpus- linguistic methods provides clearer empirical insight into Qur’anic near-synonymy within Arabic linguistic studies.